Restoration of Thoracic Kyphosis in Adolescent Idiopathic Scoliosis Over a Twenty-year Period: Are We Getting Better?. Issue 23 (1st December 2020) - Bodendorfer, Blake M.; Shah, Suken A.; Bastrom, Tracey P.; Lonner, Baron S.; Yaszay, Burt; Samdani, Amer F.; Miyanji, Firoz; Cahill, Patrick J.; Sponseller, Paul D.; Betz, Randal R.; Clements, David H.; Lenke, Lawrence G.; et al.
Abstract : Study Design: A multicenter, prospectively collected database of 20 years of operatively treated adolescent idiopathic scoliosis (AIS) was utilized to retrospectively examine pre- and postoperative thoracic kyphosis at 2-year follow-up. Objective: To determine if the adoption of advanced three-dimensional correction techniques has led to improved thoracic kyphosis correction in AIS. Summary of Background Data: Over the past 20 years, there has been an evolution of operative treatment for AIS, with more emphasis on sagittal and axial planes. Thoracic hypokyphosis was well treated with an anterior approach, but this was not addressed sufficiently in early posterior approaches. We hypothesized that patients with preoperative thoracic hypokyphosis prior to 2000 would have superior thoracic kyphosis restoration, but the learning curve with pedicle screws would reflect initially inferior restoration and eventual improvement. Methods: From 1995 to 2015, 1063 patients with preoperative thoracic hypokyphosis (<10°) were identified. A validated formula for assessing three-dimensional sagittal alignment using two-dimensional kyphosis and thoracic Cobb angle was applied. Patients were divided into 1995–2000 (Period 1, primarily anterior), 2001–2009 (Period 2, early thoracic pedicle screws), and 2010–2015 (Period 3, modern posterior) cohorts. Two-way repeated measures analysis of variance and post-hoc Bonferroni corrections were utilized with P < 0.05 considered significant. Results: Significant differences were demonstrated. Period 1 had excellent restoration of thoracic kyphosis, which worsened in Period 2 and improved to near Period 1 levels during Period 3. Period 3 had superior thoracic kyphosis restoration compared with Period 2. Conclusion: Although the shift from anterior to posterior approaches in AIS was initially associated with worse thoracic kyphosis restoration, this improved with time. The proportion of patients restored to >20° kyphosis with a contemporary posterior approach has steadily improved to that of the era when anterior approaches were more common. Level of Evidence: 3 Abstract : Pre- and postoperative 3D thoracic kyphosis of AIS patients were compared using 20 years of prospectively collected data. The proportion restored to >20°with posterior approaches has steadily improved, comparable to anterior approaches. We hypothesize that the adoption of posterior column osteotomies, differential rod contouring, and 3D correction may explain this.